Efficacy of dietary supplements on sports performance outcomes: a systematic review of evidence in elite athletes - Yu, T.; Ding, C. (Frontiers in Nutrition, 2025)
Objective: To systematically evaluate the efficacy of dietary supplements for enhancing athletic performance specifically in elite athletes, considering supplement type, dosing protocols, and sport-specific demands.